Burn Center Barrier Protocols During Dressing Change. Issue 4 (July 2015) - Meyerson, Joseph M.; Coffey, Rebecca; Jones, Larry M.; Miller, Sidney F.
<x xml:space="preserve">Abstract</x> Infection control is a critical component of post-burn care with prevention of infection serving as a major cause of decreasing morbidity and mortality. One potential deterrent for infection is barrier protection during dressing changes; however, no evidence-based standard has been established among burn centers. The purpose of this study is to describe the current barrier techniques of American burn centers. A 24-question survey was sent to 121 burn center nurse managers within the United States. The survey was comprised of yes or no questions with comment sections available for further detail. Questions were constructed to gain insight into the variation and commonality that may exist between burn center barrier protocols. Forty-one out of 121 centers (34%) responded. Centers reported the use of head covers, masks, gowns, and gloves during admission of a new burn (71%, 82%, 95%, and 100% respectively); daily dressing changes (64%, 80%, 97%, and 100% respectively); postoperative dressing changes (64%, masks 80%, 97%, and 100% respectively); and dressing changes of a nonburn (66%, 82%, 97%, and 100% respectively). Burn centers reported their use of sterile gloves and gowns during typical burn dressing changes as occurring 20% and 10% of the time, respectively. Estimates for costs of these garments annually ranged from $0 to $250, 000. A calculation performed for this study demonstrated that barrier garments used for dressing changes nationwide is approximately $2.43 million. We demonstrated the immense cost, to an institution and nationwide, of barrier garments used solely for dressing changes.